Frequentist, Bayesian Analysis and Complementary Statistical Tools for Geriatric and Rehabilitation Fields: Are Traditional Null-Hypothesis Significance Testing Methods Sufficient? - Nascimento DDC; Rolnick N; da Silva Almeida I; Cipriano Junior G; Durigan JL (Clinical Interventions in Aging, 2024)
Dahan da Cunha Nascimento,1,* Nicholas Rolnick,2,* Isabella da Silva Almeida,3,* Gerson Cipriano Junior,4,* João Luiz Durigan3,* 1Physical Education Department, Universidade Católica de Brasília, Brasília, DF, Brazil; 2The Human Performance Mechanic Department, Lehman College, Bronx, NY, USA; 3Laboratory of Muscle and Tendon Plasticity, Faculdade de Ceilândia, Universidade de Brasília, Brasília, DF, Brazil; 4Graduate Program in Rehabilitation Science, Faculdade de Ceilândia, Universidade de Brasília, Brasília, DF, Brazil*These authors contributed equally to this workCorrespondence: João Luiz Durigan, Laboratory of Muscle and Tendon Plasticity, Faculdade de Ceilândia, Universidade de Brasília, Centro Metropolitano, conjunto A, lote 01, Brasília, DF, 72220-275, Brazil, Tel/Fax +55 (61) 3376-0252, Email joaodurigan@gmail.comAbstract: Null hypothesis significant testing (NHST) is the dominant statistical approach in the geriatric and rehabilitation fields. However, NHST is routinely misunderstood or misused. In this case, the findings from clinical trials would be taken as evidence of no effect, when in fact, a clinically relevant question may have a “non-significant” p-value. Conversely, findings are considered clinically relevant when significant differences are observed between groups. To assume that p-value is not an exclusive indicator of an association or the existence of an effect, researchers should be encouraged to report other statistical analysis approaches as Bayesian analysis and complementary statistical tools alongside the p-value (eg, effect size, confidence intervals, minimal clinically important difference, and magnitude-based inference) to improve interpretation of the findings of clinical trials by presenting a more efficient and comprehensive analysis. However, the focus on Bayesian analysis and secondary statistical analyses does not mean that NHST is less important. Only that, to observe a real intervention effect, researchers should use a combination of secondary statistical analyses in conjunction with NHST or Bayesian statistical analysis to reveal what p-values cannot show in the geriatric and rehabilitation studies (eg, the clinical importance of 1kg increase in handgrip strength in the intervention group of long-lived older adults compared to a control group). This paper provides potential insights for improving the interpretation of scientific data in rehabilitation and geriatric fields by utilizing Bayesian and secondary statistical analyses to better scrutinize the results of clinical trials where a p-value alone may not be appropriate to determine the efficacy of an intervention.Keywords: statistics, statistical significance, effect size, p-value